WHAT SOFTWARE TO USE IN THE TEACHING OF MATHEMATICAL SUBJECTS? - Berezný, Stefan (Acta Didactica Napocensia, 2015)
We can consider two basic views, when using mathematical software in the teaching of mathematical subjects. First: How to learn to use specific software for the specific tasks, e. g., software Statistica for the subjects of Applied statistics, probability and mathematical statistics, or financial mathematics. Second: How to learn to use the software that is available to us to solve specific mathematical problems from different areas of mathematics and applied mathematics. My article describes the practical use of the software in the teaching of mathematical subjects and my experience with its use by the students and the pedagogues. In our computer laboratory our students use the following software: MS Office (MS Excel), LibreOffice (LO Calc), MATLAB 2010b, Octave, wxMaxima, and L^sup A^T^sub E^X. We use this software in the following mathematical subjects: Operational Analysis, Linear and Quadratic Programming, Numerical Mathematics, Applied Statistics, Queuing Theory, and Fundamentals of the L^sup A^T^sub E^X. Eight years of experience with the usage of these programs have shown us, how we can improve the teaching process of the mathematical subjects at the technical universities with freely available software.